2022
DOI: 10.3390/plants11182437
|View full text |Cite
|
Sign up to set email alerts
|

Management of Rhizosphere Microbiota and Plant Production under Drought Stress: A Comprehensive Review

Abstract: Drought generates a complex scenario worldwide in which agriculture should urgently be reframed from an integrative point of view. It includes the search for new water resources and the use of tolerant crops and genotypes, improved irrigation systems, and other less explored alternatives that are very important, such as biotechnological tools that may increase the water use efficiency. Currently, a large body of evidence highlights the role of specific strains in the main microbial rhizosphere groups (arbuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…In order to promote sustainable crop production and address concerns about the depletion of future P reserves and environmental pollution from excessive P application, it is necessary to develop an improved method of P fertilizer application. Rhizosphere-based P management has been shown to enhance PUE in highly P-xed soils by synchronizing P mineralization and uptake, minimizing P xation, and promoting early root growth (Richardson et al, 2009;Shen et al, 2011;Vidal et al, 2022;Yu et al, 2022). This approach has been supported by various interventions, such as phosphate solubilizing microorganisms (PSMs), slow-releasing P sources like rock phosphate and compost with PSM, and VAM (Hodge et al, 2009;Thakuria et al, 2009;Vassilev et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote sustainable crop production and address concerns about the depletion of future P reserves and environmental pollution from excessive P application, it is necessary to develop an improved method of P fertilizer application. Rhizosphere-based P management has been shown to enhance PUE in highly P-xed soils by synchronizing P mineralization and uptake, minimizing P xation, and promoting early root growth (Richardson et al, 2009;Shen et al, 2011;Vidal et al, 2022;Yu et al, 2022). This approach has been supported by various interventions, such as phosphate solubilizing microorganisms (PSMs), slow-releasing P sources like rock phosphate and compost with PSM, and VAM (Hodge et al, 2009;Thakuria et al, 2009;Vassilev et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They show mechanisms that involve the maintenance of the cell water homeostasis under drought conditions, allowing diminished water loss and increasing water inlet, carbon sequestration, nutrient cycling, resulting in health of crops, and rhizosphere ecosystem functioning [31,32]. Many bacterial groups have been related to these mechanisms, for example, Acinetobacter, Azospirillum, Azotobacter, Arthrobacter, Bacillus, Beijerinckia, Brevundimonas, Burkholderia, Clostridium, Delftia, Duganella, Erwinia, Enterobacter, Flavobacterium, Hydrogenophaga, Methylobacterium, Paenibacillus, Pantoea, Proteus, Providencia, Pseudomonas, Psychrobacter, Rhizobium, Serratia, Stenotrophomonas, Streptococcus, and Streptomyces [33,34].…”
Section: Drought Responsesmentioning
confidence: 99%
“…In drought-stressed plants, their growth and secondary metabolite production can be significantly affected [33]. Previous studies have reported an increase in capsaicinoid content under a water deficit [61,68].…”
Section: External Factors That Affect Capsaicinoids and Capsinoidsmentioning
confidence: 99%